Cultural Appropriateness in Health Communication: A Review and A Revised Framework. Issue 5 (4th May 2019) - Tan, Naomi Q. P.; Cho, Hyunyi
Abstract : A revised framework for cultural appropriateness is offered on the basis of a systematic review of operationalizations in 44 cancer screening interventions for Asian Americans. Studies commonly conveyed the epidemiological bases of the intervention (97.7%) and used the language of the population (95.5%). Less commonly reported were strategies central to health communication: cultural features of the intervention messages (77.3%) and the cultural beliefs and values that the intervention focused on (43.2%). Few used cultural tailoring (4.5%) and none aimed to address acculturation or cultural identity. The theoretical framework most frequently used was the health belief model (27.3%) which does not explain the role of culture. More studies focused on cultural barriers (20.5%) than cultural strengths (9.1%). Our revised framework comprises six cultural appropriateness strategies of cultural identity, linguistic, perceptual features, content, constituent-involving, and socioeconomic context-adaptive. It prioritizes cultural identity to recognize the dynamics within racial ethnic groups and to inform adaptive efforts for cultural appropriateness. It emphasizes examining cultural strengths that can facilitate change, as well as reducing cultural barriers. Future research and action should address the disparities in extant health disparities research in which theory and methods are underdeveloped and underutilized for Asian Americans.